2011
DOI: 10.1007/s00436-011-2321-8
|View full text |Cite
|
Sign up to set email alerts
|

The colonization of the invasive round goby Neogobius melanostomus by parasites in new localities in the southwestern Baltic Sea

Abstract: The round goby Neogobius melanostomus is a bottom-dwelling fish native for the Ponto-Caspian basin, which started to colonize the Baltic Sea since 1991. The parasites of this fish species in the southwestern Baltic region are studied for the first time. The round goby in the SW Baltic Sea was infected with 12 parasite species: 1 species of Microsporidia, 1 species of Monogenea, 1 of Cestoda, 3 species of Trematoda, 3 species of Nematoda, 2 of Acanthocephala, and 1 species of Bivalvia. Microsporidia genus speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
(33 reference statements)
1
23
0
Order By: Relevance
“…Digenean trematode larvae of the species Diplostomum spp. have been observed as the most prevalent parasites in many previous studies in the Baltic Sea (Kvach & Skóra, 2006;Kvach & Winkler, 2011;Kvach et al, 2014; Table 7), as well as, other native and non-native areas (Kvach & Skóra, 2006;Kvach & Stepien, 2008;Francová et al, 2011;Gendron et al, 2012). In this study, it was found to be the most common parasite with the highest prevalence and intensity in Muuga and Mariehamn (Table 3), but absent from the two other sites.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Digenean trematode larvae of the species Diplostomum spp. have been observed as the most prevalent parasites in many previous studies in the Baltic Sea (Kvach & Skóra, 2006;Kvach & Winkler, 2011;Kvach et al, 2014; Table 7), as well as, other native and non-native areas (Kvach & Skóra, 2006;Kvach & Stepien, 2008;Francová et al, 2011;Gendron et al, 2012). In this study, it was found to be the most common parasite with the highest prevalence and intensity in Muuga and Mariehamn (Table 3), but absent from the two other sites.…”
Section: Discussionsupporting
confidence: 64%
“…All parasites found in the Baltic populations have also been previously recorded in the Baltic Sea (Rolbiecki, 2006;Kvach & Winkler, 2011). Therefore, there is no indication of spillover of nonnative parasites into the Baltic Sea, which was an obvious concern knowing that some non-indigenous fish have introduced invasive and severely harmful parasites to native species (e.g.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations